Cyber Terrorism: Strategi Propaganda dan Rekrutmen ISIS di Internet Dan Dampaknya Bagi Indonesia Tahun 2014-2019 - Putri, Santi Dwi; Wahyudi, Fendy Eko (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
In a world runs by the use of technology, ISIS combines its radical interpretation ofIslam with the modernity of the internet and social media to expand its influences that havenever been reached by other extremist groups. Refers to social cognitive theory and theconcept of supernova by Thomas L.Friedman, this study finds further indicator of therelationship between internet and individual’s radicalization, and aims to answer aquestion; How ISIS spreads its ideology and recruits their members by using online mediaplatform especially in Indonesia?. In order to answer the research question, the author usesqualitative research method using observation technique and interviews the former ISISradicals who would add perspectives on how Internet changes and makes their radicalizationprocess. This phenomenom by ISIS classified as a Cyberterrorism, especially HybridCyberterrorism, which means the use of the Internet for activities such as propaganda,recruitment, radicalization, communication, training, and planning for actual terroristattacks.